Endovascular coiling of recurrent trapped pseudoaneurysm of petrous ICA across the distal barrier: When the other way round is the only way around!. Issue 5 (October 2022) - Hosur, Bharat; Ahuja, Chirag K; Tripathi, Manjul; Mohindra, Sandeep; Vyas, Sameer; Singh, Paramjeet
Background: The pseudoaneurysms of the internal carotid artery (ICA) at the skull base form a unique subset of craniofacial pseudoaneurysms with varied diagnostic and therapeutic challenges. Recurrence in a surgically treated pseudoaneurysm may become a nightmare due to very limited number of open and endovascular options. Report: We report a rare case of recurrent pseudoaneurysm of petrous ICA, which presented with massive epistaxis following an initial successful occlusion by surgical trapping of the parent arterial segment with surgical clip. Cerebral angiography revealed filling of the pseudoaneurysm by small arterial channels from the external carotid, contralateral internal carotid and basilar arterial branches and emptying through the "slipped" distal clip. After a meticulous analysis of the cerebral angiogram, the recurrent pseudoaneurysm was eventually embolized retrogradely through the "slipped" clip after crossing the anterior communicating artery taking a contralateral internal carotid access. Conclusion: Scrupulous planning and execution of ICA pseudoaneurysms is necessary to prevent recurrence. Naturally occuring collateral routes through the Circle of Willis aid in treatment of "unreachable" vascular lesions.